Effective strategies to enhance awareness and proficiency in open wound emergency management for students - Putra Agina Widyaswara Suwaryo; Dadi Santoso; Hendri Tamara Yuda; Irmawan Andri Nugroho; H. Hariyady (Universitas Muhammadiyah Malang, 2024)
Accidents can happen at home, school, day care center, or on the street at any time of the day. Children are prone to accidents or injuries because of their curiosity and vulnerability to accidents, especially at school. Accidents can include falls, choking on food, swallowing objects, electric shock, exposure to hot water, and drowning. The empowerment was carried out to increase the knowledge and skills of students in schools in providing first aid measures for open wounds. The activity was carried out at the Kota Kinabalu Indonesian School (SIKK) with 239 participants. The results of the activity showed an increase in knowledge and skills after being given education. Good knowledge and skills will improve health services and minimize the risk of injury. Similar activities can be carried out again with health topics and more diverse participants.